2022
DOI: 10.5194/egusphere-egu22-10519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptive Bias Correction for Improved Subseasonal Forecasting

Abstract: <p>Improving our ability to forecast the weather and climate is of interest to all sectors of the economy and government agencies from the local to the national level. In fact, weather forecasts 0-10 days ahead and climate forecasts seasons to decades ahead are currently used operationally in decision-making, and the accuracy and reliability of these forecasts has improved consistently in recent decades. However, many critical applications require subseasonal forecasts with lead times in between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…It is an important tool for various applications, such as agricultural planning, disaster preparedness and risk mitigation for extreme events like heatwaves, droughts, floods, and cold spells, as well as water resource management [2][3][4][5]. However, subseasonal forecasting is a challenging task due to its complex dependence on both local weather conditions and global climate system variables [6,7]. Furthermore, the subseasonal time scale has long been considered as a 'predictability desert' [8,9] as it suffers from the chaotic nature of the atmosphere [10] and the lack of predictive information from land beyond one month.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an important tool for various applications, such as agricultural planning, disaster preparedness and risk mitigation for extreme events like heatwaves, droughts, floods, and cold spells, as well as water resource management [2][3][4][5]. However, subseasonal forecasting is a challenging task due to its complex dependence on both local weather conditions and global climate system variables [6,7]. Furthermore, the subseasonal time scale has long been considered as a 'predictability desert' [8,9] as it suffers from the chaotic nature of the atmosphere [10] and the lack of predictive information from land beyond one month.…”
Section: Introductionmentioning
confidence: 99%
“…The FuXi-S2S 3 European Centre for Medium-Range Weather Forecasts (ECMWF) ensemble prediction system (EPS) [12] and the National Centers for Environmental Prediction (NCEP) Climate Forecast System version 2 (CFS v2) [13] are two leading operational subseasonal ensemble forecast systems, with 51 and 11 members, respectively. Nevertheless, these NWP forecasts exhibit considerable biases [7,14], particularly in predicting extreme events [15].…”
Section: Introductionmentioning
confidence: 99%
“…One major challenge in statistical post-processing is to retain spatial and temporal relationships in the post-processed forecasts, as well as relationships between variables (Vannitsem et al, 2021). In particular, the few examples of S2S post-processing studies that we are aware of tend to separately operate on single grid-cells only, and thus are neither able to exploit spatial information in the raw forecasts, nor produce spatially homogeneous forecasts (e.g., Vigaud et al, 2017Vigaud et al, , 2019Mouatadid et al, 2021;Zhang et al, 2023). For short-to medium-range forecasts, convolutional neural network (CNN)-based architectures and model components have been used for a variety of post-processing applications (Dai and Hemri, 2021;Grönquist et al, 2021;Veldkamp et al, 2021;Chapman et al, 2022;Lerch and Polsterer, 2022;Li et al, 2022;Ben-Bouallegue et al, 2023;Hu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the sub-seasonal range, different techniques have been used to improve temperature forecasts, including machine learning [22,23], statistical models trained on dynamical models [24], and data-driven methods using random forest techniques [25]. Under this framework, in this current study, we extended a past investigation [13] where a benchmark analysis was only shown on data of one year for sub-seasonal and seasonal forecasts of temperatures by our meteorological model.…”
Section: Introduction and Context Of Applicationmentioning
confidence: 99%
“…However, a decline in model performance was noticed between the 5th and 8th week of the prediction period. Moreover, in the sub-seasonal range, different techniques have been used to improve temperature forecasts, including machine learning [22,23], statistical models trained on dynamical models [24], and data-driven methods using random forest techniques [25].…”
Section: Introduction and Context Of Applicationmentioning
confidence: 99%